Alternol/Alteronol: Potent Anti-cancer Compounds With Multiple Mechanistic Actions - Liu, Wang; Li, Jean C.; Huang, Jian; Chen, Jiepeng; Holzbeierlein, Jeffrey; Li, Benyi (Frontiers in Oncology, 2020)
Alternol and its oxidate isomer Alteronol are small compounds isolated from the fermentation of a mutant fungus obtained from Taxus brevifolia bark. Preclinical studies showed their potent anti-cancer activities, including attenuating cellular survival pathways, altering protein levels of cell cycle regulators, activating xanthine dehydrogenase to cause accumulation of cellular reactive oxygen species and disrupting cell metabolism by disturbing four Krebs cycle enzymes specifically in malignant cells while having no significant effect on benign cells. In cancer cell culture models, Alternol or Alteronol exerts their anti-cancer effect by inducing cell cycle arrest and triggering apoptotic cell death. In mice xenograft models, Alternol or Alteronol potently suppresses tumor growth with no obvious toxicity to the host with a wide therapeutic index over 30-fold. In conclusion, Alternol or Alteronol possesses great potential and feasibility to be developed as an effective anti-tumor therapeutics.